1979
DOI: 10.1111/j.1939-0025.1979.tb02650.x
|View full text |Cite
|
Sign up to set email alerts
|

Rape: Sexual disruption and recovery.

Abstract: In a longitudinal study of 81 adult rape victims reinterviewed four to six years later, effects of the rape on subsequent sexual functioning are analyzed. Most victims who had been sexually active were found to experience changes in frequency of sexual activity and in sexual response. Interview responses of victims are reported, and suggestions are offered for the counseling of rape victims and their sexual partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 3 publications
2
52
0
1
Order By: Relevance
“…En ce qui concerne la violence faite aux femmes, Burgess et al (1979), de même que Ruch et al (1983), ont trouvé qu'un viol antérieur compliquait le processus de guérison psychologique suite à un viol. Burgess et al (1978) ont aussi trouvé que les femmes ayant subi des voies de fait mettaient plus longtemps à récupérer des suites d'un viol que celles qui n'avaient pas été exposées à cet événement.…”
Section: Etudes Soutenant L'hypothèse De La Vulnérabilité Croissanteunclassified
“…En ce qui concerne la violence faite aux femmes, Burgess et al (1979), de même que Ruch et al (1983), ont trouvé qu'un viol antérieur compliquait le processus de guérison psychologique suite à un viol. Burgess et al (1978) ont aussi trouvé que les femmes ayant subi des voies de fait mettaient plus longtemps à récupérer des suites d'un viol que celles qui n'avaient pas été exposées à cet événement.…”
Section: Etudes Soutenant L'hypothèse De La Vulnérabilité Croissanteunclassified
“…Numerous clinical studies have found a positive association between childhood sexual abuse and substance use (Burgess & Holmstrom, 1979;Rohsenow, Corbett, & Devine, 1988; Straus, 1979). For example, Singer, Petchers and Hussey (1989) found that adolescents with a sexual abuse history were more likely to use cocaine, stimulants, and other drugs regularly than the matched group without a sexual abuse history.…”
Section: Childhood Sexual Abuse and Drug Usementioning
confidence: 99%
“…This finding is consistent with other studies exploring the acknowledgement of rape and reporting rape to the police (Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Kahn, Mathie, & Torgler, 1994). Women acknowledged they had been raped when the characteristics of their rape was congruent with stereotypical rape characteristics such as stranger rape, use of high levels of force, involvement of a weapon, and resultant physical injury (Burgess & Holmstrom, 1979;Du Mont, Miller, & Myhr, 2003;Kahn et al, 1994). When a rape lacked those characteristics women did not acknowledge they had experienced rape (Kahn et al, 1994: Kahn et al, 2003.…”
Section: Decision Makingsupporting
confidence: 82%